Outcome, efficacy and safety of endovascular thrombectomy in ischaemic stroke according to time to reperfusion: data from a multicentre registry. (March 2019) - Meinel, Thomas Raphael; Kaesmacher, Johannes; Mordasini, Pasquale; Mosimann, Pascal J.; Jung, Simon; Arnold, Marcel; Heldner, Mirjam Rachel; Michel, Patrik; Hajdu, Steven D.; Ribo, Marc; Requena, Manuel; Maegerlein, Christian; et al.
Background and purpose: In acute ischaemic stroke (AIS) of the anterior circulation (AC) treated with mechanical thrombectomy (MT), data point to a decline of treatment effect with increasing time from symptom onset to treatment. However, the magnitude of the decline will depend on the clinical setting and imaging selection used. The aims of this study were (1) to evaluate the clinical effect of time to reperfusion (TTR); and (2) to assess the safety and technical efficacy of MT according to strata of TTR. Methods: Using the retrospective multicentre BEYOND-SWIFT registry data (ClinicalTrials.gov identifier: NCT03496064), we compared safety and efficacy of MT in 1461 patients between TTR strata of 0–180 min ( n = 192), 180–360 min ( n = 876) and >360 min ( n = 393). Clinical effect of TTR was evaluated using multivariable logistic regression analyses adjusting for pre-specified confounders [adjusted odds ratios (aOR) and 95% confidence intervals (95% CI)]. Primary outcome was good functional outcome (modified Rankin Scale: mRS 0–2) at day 90. Results: Every hour delay in TTR was a significant factor related to mRS 0–2 (aOR 0.933, 95% CI 0.887–0.981) with an estimated 1.5% decreased probability of good functional outcome per hour delay of reperfusion, and mRS 0–1 (aOR 0.929, 95% CI 0.877–0.985). Patients with late TTR had lower rates of successful and excellent reperfusion, higher complication rates and number of passes. Conclusions: TTR is an independent factor related to long-term functional outcome. With increasing TTR, interventional procedures become technically less effective. Efforts should be made to shorten TTR through optimized prehospital and in-hospital pathways.